A comparative analysis of the concept of intention (niyyah) in the theory of planned behaviour and Islamic jurisprudence - Ahmad Najib, Syazalie Hirman; Md. Sawari, Mohd. Fuad; Suhaimi, Abdul Hakim (Usuli Faqih Research Centre PLT, 2025)
This article compares the concept of intention (niyyah) in the Theory of Planned Behaviour (TPB) with its treatment in Islamic jurisprudence, assessing the capacity of TPB to reflect Islamic legal and spiritual dimensions. Using qualitative comparative analysis, it addresses four key questions concerning the definitions, epistemological bases, and practical implications of niyyah in both frameworks. The study finds that TPB conceptualises intention as a rational, cognitive predictor of behaviour, whereas Islamic jurisprudence regards niyyah as a legal and spiritual condition that determines the validity and reward of actions. The paper argues that TPB is inadequate in religious contexts and calls for a Maqāṣid al-Sharīʿah-based model that integrates theological, ethical, and behavioural elements. It recommends the contextual adaptation of behavioural theories, and the development of models rooted in Islamic epistemology